Projeto InVision Framework: Um framework para suportar a criação e uso de jogos no ensino - ALVES, Daniel Ferreira Monteiro (2011)
The number of people joining the Computer Science course, in the last years, is decreasing. Among those who enter, just a few are able to graduate, because there is a great retention rate and dropout, particularly among the introductory courses in algorithms and programming. The use of games as a motivational factor is a subject much studied in recent years, achieving good results for this problem. However, for the implementation of games in education, using a constructionist approach, students are required to build games. Several tools are available for this job, but there is a big difference in usability between the educational tools (that focus on educational programming) and those specific for creating games. This work proposes a framework for building games, being supported by an extensible application through scripts which allow it to be adapted for use in various disciplines throughout the course, and not only in introductory courses.